The cut-off analysis using visual analogue scale and cepstral assessments on severity of voice disorder. (2nd October 2018) - Lee, Yeon Woo; Kim, Geun Hyo; Bae, In Ho; Park, Hee June; Wang, Soo Geun; Kwon, Soon Bok
Abstract: Purpose: The aims of this study were to: (1) determine the visual analogue scale (VAS) and cepstrum peak prominence (CPP) cut-off points on the ratings of numerical scale (NS) related to the severity of voice disorder ratings and (2) verify the discriminative power of these cut-off points for distinguishing between different severities of voice disorder. Methods: Auditory-perceptual severity assessments (VAS and four-point NS) of 214 voice samples were performed by three speech-language pathologists and CPP parameters were used for the acoustic analysis. Both VAS and CPP cut-off points were obtained using receiver operating characteristic (ROC) curve analyses, based on their correspondence with NS ratings. Results: A high level of inter- and intra-rater reliability was found for the auditory-perceptual assessments of both VAS and NS. The VAS cut-off points for overall severity (OS), between normal variation and mild/moderate severity, mild/moderate and moderate severity, and moderate and severe severity were 32.7, 51.7, and 71.7 points, respectively, and CPP cut-off points were 7.050, 4.651, and 2.989 points, respectively. Areas under the ROC curves demonstrated excellent specificity and sensitivity of all cut-off points. Conclusions: The VAS and CPP cut-off points of OS of voice disorder demonstrated a high power to discriminate between different severities of voice disorder. The results of this study suggested cut-off points for clinical use.